Reconstruction of paralyzed arm function in patients with hemiplegia through contralateral seventh cervical nerve cross transfer: a multicenter study and real-world practice guidance. (January 2022) - Feng, Juntao; Li, Tie; Lv, Minzhi; Kim, Sangsoo; Shin, Joon-Ho; Zhao, Naiqing; Chen, Qingzhong; Gong, Yanpei; Sun, Yucheng; Zhao, Zaixing; Zhu, Ning; Cao, Jihua; et al.
Summary: Background: A previous randomized controlled trial showed contralateral seventh cervical nerve (CC7) cross transfer to be safe and effective in restoring the arm function of spastic arm paralysis patients in a specified population. Guidance on indications, safety and expected long-term improvements of the surgery are needed for clinical practice. Methods: This is a retrospective, multicenter, propensity score-matched cohort study. All patients registered between 2013 and 2019 with unilateral spastic arm paralysis over 1 year who were registered at one of five centers in China and South Korea were included. Patients received CC7 cross transfer or rehabilitation treatment in each center. Primary outcome was the change in the upper-extremity Fugl–Meyer (UEFM) score from baseline to 2-year follow-up; larger increase indicated better functional improvements. Findings: The analysis included 425 eligible patients. After propensity score matching, 336 patients who were 1:1 matched into surgery and rehabilitation groups. Compared to previous trial, patient population was expanded on age (< 12 and > 45 years old), duration of disease (< 5 years) and severity of paralysis (severe disabled patients with UEFM < 20 points). In matched patients, the overall increases of UEFM score from preoperative evaluation to 2-year follow-up were 15.14 in the surgery group and 2.35 in the rehabilitation group (difference, 12.79; 95% CI: 12.02–13.56, p < 0.001). This increase was 16.58 at 3-year and 18.42 at 5-year follow-up compared with the surgery group baseline. Subgroup analysis revealed substantial increase on UEFM score in each subgroup of age, duration of disease, severity of paralysis and cause of injury. No severe complication or disabling sequela were reported in the surgery group. Interpretation: This study showed that CC7 cross transfer can provide effective, safe and stable functional improvements in long-term follow-up, and provided evidences for expanding the indications of the surgery to a wider population of patients with hemiplegia.